HUBUNGAN PAPARAN DEBU TERHIRUP DENGAN GANGGUAN FUNGSI PARU PADA PEKERJA PERTAMBANGAN PASIR DAN BATU PERUSAHAAN X ROWOSARI KOTA SEMARANG - Apsari, Laeila; Budiyono, Budiyono; Setiani, Onny (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Thetsand and stone mining industry has potential to produced a dust. The dust that produced has potential exposure to their workers and caused lung function disorder. The concentrations of total dust, PM10, PM2.5 were 224.3 μg/Nm3,181.7 μg/Nm3 and 153.7 μg/Nm3. This study aimed to analyzed associationtbetween respirable dusttand lung functiontdisorder ontsand and rock mining workers at X Company Rowosari, Semarang City. Thistwas antobservationaltresearch withtcross sectional designtwith totaltsample 31 people. This research was conducted at Rowosari Semarang City with research instrument as questionnaire to interview personal characteristic, personal dust sampler to measure exposure of personal respirable dust and spirometer for pulmonary function test. Data were analyzedtusing thetChi SquaretTest at α = 5% . Results showed that 38.7% of workers had lung function disorder (25.8% restriction, and 12.9% obstruction). Duration of exposure to dust tended to be a risk of lung funcition disorder at sand and rock mining workers (p=0.046; PR=5.238; 95%CI=0.78-35.15). The variables that tended to be a risk factor of lung function disorder were nutritional status (p=1.00; PR=1,153; 95%CI=0.46-2,85), working period (p=0,691; PR=1,444; 95%CI=0.55 -3,79) and exercise habits (p=1.00; PR=1.179; 95%CI=0.22-6.23). Variables that to be a protective factor were respirable dust exposure (p=1.00; PR=0.989; 95%CI=0.4-2.43), age (p=1.00; PR=0,875; 95%CI=0,32-2,38), smoking habit (p=0,139; PR=0,556; 95%CI= 0,39-0,78) and use of PPE (p= 1.00; RP= 0.875; 95%CI=0,32-2,38). The conclusiontof this studytthere is no association between respirable dust exposure and lung function disorder on sand and rock mining workers at X Company in Rowosari Semarang City.